Legal Review of the Late Notification of Acquisition of Commission for Supervision of Business Competition (Study of KPPU Case Decision No: 07/KPPU-M/2018) - Hari Sutra Disemadi; Agung Sujati Winata (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2020)
The form of economic activity carried out by entrepreneurs is the acquisition of shares. Takeover is a way of developing an existing company or saving a company that is experiencing capital shortages or difficulties. One of the companies that made the acquisition was PT Nippon Indosari Corpindo, Tbk. The company that has been acquired is PT. Prima Top Boga on January 24, 2018. The type of legal research used is legal research which is included in the normative legal research typology where this study focuses on positive legal norms in the form of legislation. The purpose of this study is to find out the legal analysis of the delay in notification (acquisition) of PT. Prima Top Boga by PT. Nippon Indosari Corpindo, Tbk., to KPPU and knows the stages of notification and evaluation of MPU for the acquisition of a company. The results of this study show, PT. Nippon Indosari Corpindo, Tbk., Has been proven to be slow in notifying acquisition of KPPU as stipulated in Law No. 5 of 1999 jo. Government Regulation No. 57 of 2010. Business actors wishing to make notifications regarding acquisitions that result in assets and/or sales value exceeding the stipulated provisions are required to carry out consultations as well as notifications according to the stages available.